PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN DIMSUM RATU TULUNGAGUNG - Febiana Fauziah Latif (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2022)
The development of fast food restaurants is very much encountered especially in Indonesia in this increasingly sophisticated era. Therefore, competing in the fast food business is very tight and is required to follow the pattern of technological developments and times. Service quality is a major factor in the success of a company and can also affect customer satisfaction because of the interaction between consumers and companies that can work together. In addition to service quality, price perception also affects customer satisfaction. This study aims to determine the effect of service quality and price on customer satisfaction at Dimsum Ratu Tulungagung. The data collection method used in this study is a questionnaire and data analysis using multiple linear regression. The results of the t-test research proved that (Service Quality X1) tcount > ttable (7.003 > 1.98472) and (Price X2) tcount > ttable (4.998 > 2.00856) it can be partially concluded that